Mediation effect of gut microbiota on the relationship between physical activity and carotid plaque - Ouyang, Wenbin; Tang, Bei; He, Yongmei; Wu, Hao; Yang, Pingting; Yin, Lu; Li, Xiaohui; Li, Ying; Huang, Xin (Frontiers in Microbiology, 2024)
Background: Physical activity has been shown to have an effect on Carotid plaque (CP) which is a predictor of Cardiovascular disease (CVD). Studies have shown that physical activity can alter the composition of gut microbiota, whether its influence on CP was mediated by gut microbiota has yet to be proved. Methods: We conducted a case-control study involving 30 CP patients and 31 controls. Logistic regression was used to analyze the association between CP and physical activity. LefSe was used to explore the association between gut microbiota and physical activity as well as CP, and PhyloMed was used to examine the mediating effect of gut microbiota in the association between physical activity and CP. Results: After adjusting for potential confounders, adequate physical activity showed a significant association with a decreased risk of CP (OR adj: 0.25, 95%CI: 0.06, 0.97). CP was associated with enrichment in the order Bacteroidales within the phylum Bacteroidetes and the predominant microbiota in individuals without plaque was the order Clostridiales (LDA scores > 3). Individuals with adequate physical activity had a higher abundance of the order Clostridiales, while the order Bacteroidetes was enriched in individuals with inadequate physical activity (LDA scores > 3). The PhyloMed revealed a significant mediation effect of gut microbiota in the association between physical activity and CP (P = 0.03). Conclusions: Adequate physical activity was significantly associated with a decreased risk of CP, and this association was mediated by an increase in the abundance of gut microbiota in the order Clostridiales.